2013
DOI: 10.5539/jms.v3n3p115
|View full text |Cite
|
Sign up to set email alerts
|

Web Communications of Environmental Sustainability Initiatives at Sport Facilities Hosting Major League Soccer

Abstract: We are living in times of tremendous ecological change (Winn & Kirchgeorg, 2005). In response, the United Nations (UN) promotes a movement towards safeguarding the natural environment or environmental sustainability (ES). Sport has not been immune from the challenges of ES and, thus, the guiding research question of the current investigation was: How does sport communicate its participation in environmental sustainability (ES)? To answer this research question this study focused on sport facilities that were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…total waste generated, tons diverted and tons recycled) are simple to establish a benchmark and lead to the development of higher order strategic plans and adoption of more advanced environmental innovations. The efforts themselves offer a platform to develop foundational communication platforms and information to diffuse and to communicate to stakeholders (Casper, Pfahl, and McSherry 2012;Ciletti et al 2010;McCullough 2013;Mallen, Chard, and Sime 2013;Pfahl et al 2015). Such a situation makes the first wave a strong link with the diffusion process of environmental action in sport.…”
Section: Wave Onementioning
confidence: 99%
“…total waste generated, tons diverted and tons recycled) are simple to establish a benchmark and lead to the development of higher order strategic plans and adoption of more advanced environmental innovations. The efforts themselves offer a platform to develop foundational communication platforms and information to diffuse and to communicate to stakeholders (Casper, Pfahl, and McSherry 2012;Ciletti et al 2010;McCullough 2013;Mallen, Chard, and Sime 2013;Pfahl et al 2015). Such a situation makes the first wave a strong link with the diffusion process of environmental action in sport.…”
Section: Wave Onementioning
confidence: 99%
“…Researchers have explored not only the breadth of environmental initiatives, in general, and how the industry as a whole addresses environment sustainability initiatives [36], but they have also focused on how sport organizations communicate these environmental initiatives [38]. For example, Mallen and colleagues focused on MLS facilities, analyzing environmental communications on the website of each team's venue.…”
Section: Environmental Communication In Sportmentioning
confidence: 99%
“…To this end, Francis and colleagues [37] analyzed the same websites as Mallen et al [38] with the purpose of identifying the areas in which the teams were incorporating environmental sustainability. Francis et al found that existing environmental initiatives were grouped into the following categories: stadium design, efficiency and functionality, waste reduction, sustainable food options, community outreach, and waste management (i.e., composting, recycling).…”
Section: Environmental Communication In Sportmentioning
confidence: 99%
“…Communication of renewable energy initiatives to the numerous stakeholder groups associated with an organization therefore should be a managerial priority. Indeed, the prioritizing of sustainability communications as a tool for shaping brand perceptions has been acknowledged before [9,10].…”
Section: Open Accessmentioning
confidence: 99%
“…Indeed, brand managers must take control over every organizational touch point to manage how the brand is perceived. Indeed, -utilizing all organization-to-stakeholder communication channels (i.e., web communications) to promote brand-building initiatives could assist in enhancing brand loyalty‖ [9].…”
Section: Open Accessmentioning
confidence: 99%